Investigation of Religious Moderation Values through Teacher Learning at Sidomakmur State Elementary School Students - Hartati, Yani; Mustofa, Ihsan; Jaenullah, Jaenullah (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This research aims to analyze the instillation of religious moderation values through the learning of Islamic Religious Education (PAI) teachers in Sidomakmur State Elementary School students, Way Panji District, South Lampung Regency. Religious moderation is an important issue in the context of Indonesia's diversity, especially in forming attitudes of tolerance, balance and respect for differences among students. The research method used is qualitative with a case study approach. Data was collected through observation, in-depth interviews with PAI teachers, students and school stakeholders, as well as analysis of documents related to the curriculum and learning materials. The research results show that PAI teachers play a crucial role in instilling the values of religious moderation through inclusive, dialogical and contextual learning approaches. Values such as tolerance, justice, balance, and respect for differences are integrated in teaching materials, religious activities, and daily interactions at school. Obstacles faced include limited time, students' lack of understanding of the concept of moderation, as well as challenges in aligning moderation values with students' social environment. The main contribution of the findings of this research lies in the concrete mapping of PAI teachers' effective learning strategies in instilling the values of religious moderation at the elementary school level. These findings provide a new perspective that religious moderation can be taught systematically from an early age, not just at secondary or higher education levels. This research also strengthens the urgency of PAI teacher training in developing materials and methods that support the formation of students' moderate character.